Does participating in a panel survey change respondents' labor market behavior? - Ruben L. Bach; Stephanie Eckman (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
Panel survey participation can bring about unintended changes in respondents' behavior and/or reporting of behavior. Using administrative data linked to a large panel survey, we analyze changes in respondents' labor market behavior. We estimate the causal effect of panel participation on the take-up of federal labor market programs using instrumental variables. Results show that panel survey participation leads to a decrease in respondents' take-up of these measures. These results suggest that panel survey participation not only affects the reporting of behavior, as previous studies have demonstrated, but can also alter respondents' actual behavior. – – Die wiederholte Teilnahme an Längsschnittstudien kann zu unbeabsichtigten Verhaltensänderungen und/oder Änderungen im Antwortverhalten der Teilnehmer führen. Um solchen Verhaltensänderungen nachzugehen, haben wir Umfragedaten der Längsschnittstudie PASS mit administrativen Daten verknüpft und schätzen mittels Instrumentenvariablen den kausalen Effekt der wiederholten Umfrageteilnahme auf die Teilnahme an Maßnahmen der aktiven Arbeitsmarktpolitik. Die Ergebnisse deuten darauf hin, dass Umfrageteilnehmer aufgrund der (mehrmaligen) Teilnahme an der Befragung an weniger Maßnahmen der aktiven Arbeitsmarktpolitik teilnehmen. Diese Resultate verdeutlichen, dass die wiederholte Teilnahme an Längsschnittbefragungen sich nicht nur auf das Antwortverhalten der Teilnehmer auswirken kann, sondern auch auf deren tatsächliches Verhalten.
Keywords: C83; J64; 330; Administrative Data; Longitudinal Data; Panel Conditioning; Instrumental Variable; Treatment Effects